A Secure Authentication and Key Agreement Scheme in Smart Home. Issue 2 (August 2019) - Song, Dawei; Wen, Fengtong
Abstract: Secure communication between users and devices is an important aspect of IoT applications. Smart home is an emerging key element in IoT applications. Due to limited computing resources, it is difficult to deal with these communication problems. Therefore, a safe and efficient solution is needed to complete the communication between users and devices. Sometimes secure communication of information is required between devices and devices. In view of this point, this paper proposes a secure and efficient authentication and session key negotiation scheme between smart home devices.